2023
DOI: 10.3390/ijms24065553
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of the Class IIa HDAC Inhibitor CHDI0039 with Bortezomib in Head and Neck Cancer Cells

Abstract: In contrast to class I/IIb/pan histone deacetylase inhibitors (HDACi), the role of class IIa HDACi as anti-cancer chemosensitizing agents is less well understood. Here, we studied the effects of HDAC4 in particular and the class IIa HDACi CHDI0039 on proliferation and chemosensitivity in Cal27 and cisplatin-resistant Cal27CisR head and neck squamous cell cancer (HNSCC). HDAC4 and HDAC5 overexpression clones were generated. HDAC4 overexpression (Cal27_HDAC4) increased proliferation significantly compared to vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Class I HDAC1 Expression levels: up-regulated expression in LSCC samples [36] and HNSCC samples according to TCGA, CPTAC and HPA databases Cell proliferation: regulating the expression of PCNA and affecting cell proliferation by reducing Mrna stability [37] Invasion and metastases: interacting with RAR-α to regulate OSCC EMT and invasion through RAR-β [38]; associated with lymph node metastases and advanced clinical stage in LSCC [36] Cell death: acting as a central gene in autophagy process in HNSCC [39] Therapy resistance: down-regulated expression in cisplatin-resistant HNSCC, inversely associated with adhesion loss and drug resistance [40] HDAC2 Expression levels: positive HDAC2 nuclear staining was detected in 80/93 OSCC samples and 11/20 OED samples [41] Cell proliferation: associated with transcriptional repression and tumor maintenance in SCC [47] Invasion and metastases: maintaining HIF-1α stability, promoting cell invasion and metastases of oral cancer [44]; correlated with adhesion loss and aggressiveness, promoting the occurrence and depth of invasion in OSCC [32,42] Cell death: playing a significant role in trichodermin [45] orγ-bisabolene [46] induced apoptosis in HNSCC HDAC3 Immunosuppression: acting as the target of PKM2-mediated immunosuppression in HNSCC [49] HDAC8 Expression levels: up-regulated expression in OSCC [44] and HNSCC samples according to TCGA database Cell death: knocking down HDAC8 induce apoptotic cell death through caspase activation and autophagy in OSCC [51,52] Class II HDAC4 Expression levels: up-regulated expression in NPC [55], Cal27 [56] and ESCC [57] cells, but the TCGA, CPTAC and HPA databases revealed a down-regulated expression in HNSCC, indicating that HDAC4 may possess dual roles in cancer development…”
Section: Classification Hdac Targets and Mechanisms In Hnsccmentioning
confidence: 99%
See 4 more Smart Citations
“…Class I HDAC1 Expression levels: up-regulated expression in LSCC samples [36] and HNSCC samples according to TCGA, CPTAC and HPA databases Cell proliferation: regulating the expression of PCNA and affecting cell proliferation by reducing Mrna stability [37] Invasion and metastases: interacting with RAR-α to regulate OSCC EMT and invasion through RAR-β [38]; associated with lymph node metastases and advanced clinical stage in LSCC [36] Cell death: acting as a central gene in autophagy process in HNSCC [39] Therapy resistance: down-regulated expression in cisplatin-resistant HNSCC, inversely associated with adhesion loss and drug resistance [40] HDAC2 Expression levels: positive HDAC2 nuclear staining was detected in 80/93 OSCC samples and 11/20 OED samples [41] Cell proliferation: associated with transcriptional repression and tumor maintenance in SCC [47] Invasion and metastases: maintaining HIF-1α stability, promoting cell invasion and metastases of oral cancer [44]; correlated with adhesion loss and aggressiveness, promoting the occurrence and depth of invasion in OSCC [32,42] Cell death: playing a significant role in trichodermin [45] orγ-bisabolene [46] induced apoptosis in HNSCC HDAC3 Immunosuppression: acting as the target of PKM2-mediated immunosuppression in HNSCC [49] HDAC8 Expression levels: up-regulated expression in OSCC [44] and HNSCC samples according to TCGA database Cell death: knocking down HDAC8 induce apoptotic cell death through caspase activation and autophagy in OSCC [51,52] Class II HDAC4 Expression levels: up-regulated expression in NPC [55], Cal27 [56] and ESCC [57] cells, but the TCGA, CPTAC and HPA databases revealed a down-regulated expression in HNSCC, indicating that HDAC4 may possess dual roles in cancer development…”
Section: Classification Hdac Targets and Mechanisms In Hnsccmentioning
confidence: 99%
“…Cell death: playing roles in regulating EBV lytic replication and cell death [56] HDAC7 Cell proliferation: HDAC7 knockdown resulted in growth suppression through G2/M arrest in MEC [63]; targeting of HDAC7 could potentially disrupt the miR-4465-EphA2 pathway and impede the progression of NPC [64] Invasion and metastases: target of miR-140-5p mediated invasion and migration suppression of TSCC [62] Cell death: HDAC7 knockdown in MEC promote the apoptosis and autophagy process [63] HDAC9 Expression levels: up-regulated expression in OSCC [34] Cell proliferation: promoting OSCC carcinogenesis by targeting transcription factor MEF2D and pro-apoptotic factor NR4A1/ Nur77 [34] Cell death: low expression of HDAC9 lead to G0/G1 cycle arrest in OSCC cells and increase cell apoptosis [34] HDAC6 Expression levels: down-regulated expression according to TCGA, CPTAC and HPA databases, however, Sakuma et al [69] observed HDAC6 expression increased in OSCC Cell proliferation: miR-433 downregulate HDAC6 expression by targeting its 3′UTR, leading to the inhibition of OSCC cell growth [71]; miR-206 impede proliferation of HNSCC cells through targeting HDAC6 through PTEN/AKT/Mtor signal [72] Cell death: related to autophagy and mediates the regulation between ER stress and autophagy [34] Prognostic significance: negative associations between HDAC6 expression and the OA of OSCC patients [73]; significant differences in HDAC6 expression between early stage and advanced stage OSCC samples [69] Therapy resistance: pharmacological target for overcoming chemotherapy resistance and preventing OSCC recurrence [34] HDAC10 Expression levels: TCGA database analysis showed HDAC10 expression was increased in HNSCC samples…”
Section: Classification Hdac Targets and Mechanisms In Hnsccmentioning
confidence: 99%
See 3 more Smart Citations